Screening of Ethiopian sorghum (Sorghum bicolor) landraces for their performance under Striga hermonthica ‐infested conditions. (5th September 2017) - Abate, Mesfin; Hussien, Temam; Bayu, Wondimu; Reda, Fasil
Abstract: Striga hermonthica is a major constraint to sorghum production and productivity in sub‐Saharan Africa, Ethiopia, in particular. The objectives of this study were to evaluate the performance of 49 sorghum genotypes based on their reaction to S. hermonthica and investigate the relationships among yield and Striga resistance traits, including the Striga emergence count, area under Striga number progress curve, area under Striga severity progress curve, grain yield under infested, grain yield under non‐infested conditions and relative yield loss. The genotypes differed significantly in all measured parameters under Striga‐infested and non‐infested conditions. The genotypes 'Birhan', 'Gubiye', Wolegie, Zegerie, Nechmashila I, Woftel, Tetron and Eyssa were identified as promising ones based on grain yield and Striga‐ related traits. On the other hand, the genotypes Jamyo, Bobie, Gedido, Mankebar and Zengada had moderate Striga numbers with low relative yield loss as compared with susceptible checks. The most promising variety, Zegerie, Mankebar and Zengada, out yielded the standard resistant checks 'Birhan' and 'Gubiye' under Striga infestation. Ward cluster analysis grouped the 49 sorghum genotypes in to four distinct clusters under Striga‐infested conditions. All members of clusters II and III showed the highest yielding group with the lowest to moderate Striga number, while cluster IV supported the lowest yield with the highest Striga number. Significant negative correlations were observed between yield‐ and Striga‐ related traits. Highly significant and strong correlations were observed among Striga resistance indices, indicating that any of the Striga resistance parameters can be used as an indicator of resistance. The wide variations in grain yield among genotypes under Striga‐infested conditions would be invaluable genetic resources for production in Striga endemic areas of Ethiopia.